Studies in The Islamic Law of Contracts: The Prohibition of Gharar - Ahmad Hidayat Buang (International Law Book Service, 2000)
this book focuses on the discussion of islamic prohibition of gharar which is said to be one of the three elements that makes islamic contracts abhor modern transaction